Standardization of Coagulation Factor V Reference Intervals, Prothrombin Time, and Activated Partial Thromboplastin Time in Mice for Use in Factor V Deficiency Pathological Models - De Pablo-Moreno, Juan A.; Liras, Antonio; Revuelta, Luis (Frontiers in Veterinary Science, 2022)
Factor V together with activated factor X forms the prothrombinase complex, which transforms prothrombin into thrombin. The Mus musculus species is characterized by very high levels of this factor and short clotting times, which hinders accurate measurements. For that reason, a detailed characterization of such parameters is indispensable. A method was designed as part of this study to provide an accurate determination and standardization of factor V levels, prothrombin time and activated partial thromboplastin time in Mus musculus. Those parameters were evaluated in a sample of 66 healthy animals using a semi-automated coagulometer and human diagnostic reagents in an attempt to determine the most appropriate time of day for the extractions. A mouse-based protocol was designed, capable of making corrections to the samples at dilutions of 1:100 for factor V and at of 1:3 for prothrombin time. The goal was to smoothen the calibration curves, which often present with steep slopes and narrow measurement ranges between one calibration point and another. It was found that the most stable period for blood sample extraction was that comprised between the first six hours of light. No clinical differences were observed between the sexes and reference intervals were established for factor V (95.80% ± 18.14; 25.21 seconds ± 1.34), prothrombin time (104.31% ± 14.52; 16.85 seconds ± 1.32) and activated partial thromboplastin time (32.86 seconds ± 3.01). The results obtained are applicable to human or veterinary biomedical research, to transfusional medicine or to pathological models for diseases such as factor V deficiency.